Exploring cyber misogyny and women journalists’ work and practice in South Africa - Nyamweda, Tarisai L. (University of the Witwatersrand, Johannesburg, 2024)
Women journalists are increasingly facing cyber misogyny. However, there is a paucity of research and evidence, particularly in the global South, on this worrying phenomenon. This research study contributes to the existing body of knowledge on cyber misogyny and its effect on women journalists’ practice through documenting their experiences of cyber misogyny and how it affects journalism work and practice as well as contribute to new insights on recommendations to deal with the issue. It uses in depth interviews with selected media development and feminist organisations to understand the phenomenon of cyber misogyny as it relates to women journalists who have encountered cyber misogyny, to collect information to inform this study. Data collected has been augmented by content analysis of selected X posts generated by journalists and the responses from audiences on the selected X posts. The data collected from the in-depth interviews was analysed using inductive thematic analysis. The research is grounded on feminist theory, the concept of the role of the media in democracy and hegemonic masculinity, and uses the concept of journalistic routines as a lens through which to examine the effects of cyber misogyny on journalism practice.
A research report submitted in fulfillment of the requirements for the Master of Arts, In the Faculty of Humanities, School of Literature, Language and Media, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Cyber misogyny; Women journalists; Gender; Online violence; Social media; Harassment; South Africa; SDG-5: Gender equality